Análise do dano muscular, pico de torque, fadiga e assimetria em diferentes métodos de treino de força - Barros, Natalie de Almeida (2017)
Introduction: Strength training has been gaining more and more followers due to the benefits it has brought to health in both prevention and treatment of various pathologies. Among the different types of strength training, the following stand out: Kaatsu and traditional training. Both have gains in terms of strength gain and hypertrophy. Aims: Analyze muscle damage, peak torque, fatigue and asymmetry in different strength training methods. Methods: The study sample consisted of 10 males aged between 18 and 25 years old who had been practicing strength training for at least 12 months. All were subjected to two types of strength training, performed in Leg Press 45 ° apparatus. Venous blood was collected to analyze muscle damage indicators, before, immediately after, 24 and 48 hours after the training, as well as thermographic images collection to analyze the thermal asymmetry of the exercised limbs. Results: The results showed that the use of the Kaatsu method promoted greater muscle damage, higher fatigue index and lower torque peak immediately after training, compared to the same time in the traditional method. CK concentrations were 1093U/l in the Kaatsu method and 447,80U / l in the traditional method. As for the peak torque, it decreased after exercise to 755.38N /m in the Kaatsu method and 936, 28N /m in the traditional method. The fatigue index presented an increase of 58.28% and 37.30% in relation to the pre training in the Kaatsu and traditional methods, respectively. Regarding thermography, asymmetry found bilaterally can be considered normal, although isolated cases should be observed with more attention, considering parameters described in the literature. Conclusion: Kaatsu method promoted greater muscle damage, higher fatigue index and lower peak torque when compared to the traditional method, although it presented a faster recovery. Further research on these methods is needed to make these trainings safer and more effective for practitioners.